2005
DOI: 10.1161/01.hyp.0000174591.42889.a2
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Inhibitors and Calcium Channel Blockers for Coronary Heart Disease and Stroke Prevention

Abstract: Abstract-We investigated whether protection from coronary heart disease (CHD) and stroke conferred by angiotensinconverting enzyme inhibitors (ACEIs) and calcium channel blockers (CCBs) in hypertensive or high-risk patients may be explained by the specific drug regimen. We extracted summary statistics regarding CHD and stroke from 28 outcome trials that compared either ACEIs or CCBs with diuretics, ␤-blockers, or placebo for a total of 179 122 patients, 9509 incident cases of CHD, and 5971 cases of stroke. CHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
149
2
22

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 292 publications
(182 citation statements)
references
References 56 publications
9
149
2
22
Order By: Relevance
“…In vitro and in vivo studies in animals and humans showed that the blood-pressure-lowering action of indapamide not only involves increased natriuresis but inhibition of the contractile responses of vascular smooth muscle cells to vasopressors and adrenergic stimulation as well. 16,18 Diuretics 21,22 and calcium channel blockers 22,23 probably have a small 5-10% benefit beyond blood pressure lowering in the prevention of stroke. Unlike thiazide diuretics, indapamide, 18,24,25 as well as calcium channel blockers, inhibit the inward current of calcium across cell membranes and reduce intracellular calcium concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies in animals and humans showed that the blood-pressure-lowering action of indapamide not only involves increased natriuresis but inhibition of the contractile responses of vascular smooth muscle cells to vasopressors and adrenergic stimulation as well. 16,18 Diuretics 21,22 and calcium channel blockers 22,23 probably have a small 5-10% benefit beyond blood pressure lowering in the prevention of stroke. Unlike thiazide diuretics, indapamide, 18,24,25 as well as calcium channel blockers, inhibit the inward current of calcium across cell membranes and reduce intracellular calcium concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out in the paper, the average systolic BP difference between the CCB group and β-blocker group would have been expected to provide a difference of 4%-8% for coronary events and 11%-14% for strokes, based on previous clinical trials and epidemiologic studies. 2,3 In fact, there was a mean 13% decrease in total coronary end points (95% confidence interval [CI], 4%-21%) and 23% for stroke (95% CI, 11%-34%). This would suggest a benefit beyond BP differences.…”
Section: Discussionmentioning
confidence: 99%
“…25 Furthermore, metaregression analyses have suggested that, at a projected absence of any blood pressure reduction by treatment, ACE inhibitors retained a substantial ability to reduce the incidence of heart failure and coronary heart disease, whereas neither ACE inhibitors and angiotensin II receptor blockers retained the ability to reduce stroke, the protection against which appeared thus to be strictly blood pressuredependent. [34][35][36][37] Comparison between the cardioprotective effects of an ACE inhibitor and an angiotensin II receptor antagonist-based treatment has been recently evaluated in the Ongoing Telmisartan Alone and in combination with Ramipril Global Endpoint Trial (ONTARGET), 38 which, together with the Telmisartan Randomised AssessmeNT Study in ACE INtolerant subjects with cardiovascular Disease (TRASCEND), 39 represents the largest trial ever performed in the field of cardiovascular protection. The results of ONTARGET trial unequivocally show that telmisartan has the same efficacy, in terms of cardiovascular protection (reduction in myocardial infarction, stroke and hospitalization for congestive heart failure ( Figure 3), of ramipril, although guaranteeing a better tolerability profile (Figure 4).…”
Section: Angiotensin II Receptor Blockers Versus Ace Inhibitors On Hamentioning
confidence: 99%